Malaysian land law and procedure - Maidin, Ainul Jaria; Syed Abdul Kader, Sharifah Zubaidah (Thomson Reuters Asia Sdn. Bhd. (201801016202), 2022)
The book provides a concise and comprehensive up-to-date explanation on concepts and principles of land law for the benefit of law students, legal practitioners, legal and judicial services, inhouse lawyers and others seeking to gain understanding of the Malaysian land law as embodied in the National Land Code (Revised 2020) (Act 828). A useful textbook for those interested to know more about the Torrens system as applicable in the Malaysian land administration system in Peninsular Malaysia, the book focuses on explaining statutory provisions of the major areas of land law supported by case law and supplemented with discussion on the procedural parts.